Prioritization of Tourism Destinations Through the South Coast Lines of the Caspian Sea from Sustainable Viewpoint - Monavari, S.M.; Farshchi, P.; Karbassi, A.; Abedi, Z.; Hakimi Abed, M. (Asian Journal of Chemistry, 2011)
Sustainable tourism aims at development of tourism in such a way that avoids damage to the environment, economy and culture of the indigenous people. It requires simultaneous considering lots of criteria including infrastructure, competitiveness and supply, socioeconomic, land use/ tourist facilities and service to meet the concept of sustainable development. In the meanwhile, the southern coastal strip of the Caspian sear grabs the tourists' attention in such a volume that is considered as the main pole of tourism industry in Iran. The question now is that which areas are the best candidate destinations to establish sustainable coastal tourism. Accordingly, the current study focuses on determining and prioritizing potential destinations for sustainable coastal tourism. Thereby, site selection analysis was initially conducted using Boolean logic to find out the suitable areas. The results obtained from the research revealed that totally 15 destinations were suitable for sustainable tourism development. Afterwards, the considered destinations were separately prioritized from socio-economic, environmental, land use, tourist service and infrastructures points of view.